THE INFLUENCE OF PARENTAL UPBRINGING ON THE READING DIFFICULTIES - Hamsiah, Andi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine and obtain information about the parenting of parents against reading difficulties in elementary school students Grade 4. The study was conducted at SD Inpres Rantekombiling. This type of research is a qualitative research with a descriptive approach and the basic material is the study of literature. The population of the study was 28 student Class 4 of the 2023/2024 academic year with a sample that will be used as research, namely 2 students who are fluent in reading and students who have difficulty reading. collection techniques are by observation, interview, and documentation. One of the factors that cause children to have difficulty reading is the parenting style of both parents who pay less attention to their children to guide them in learning. The results obtained that students who experience difficulty reading in elementary school students in the upper grades get less supportive parenting and less attention from his parents. Another case with students who are fluent in reading, get good treatment from their parents and get support for the child in learning both at home and at school.